Transparansi Keuangan Gereja Sebagai Pilar Integrasi: Studi Atas Kasus Penyalahgunaan Dana - Erlangga Saputra; Joni Illu; Desti meliana Mangngi Kale; Selviana Ina Kii (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to examine the role of financial transparency as a foundation in maintaining the integrity and accountability of the church as a non-profit organization. Using a qualitative approach through literature study, data were obtained from various literature such as books, scientific articles, social media, and reports of cases of misuse of funds in the church environment. The results of the study indicate that transparency in church financial reporting plays an important role in building congregational trust, preventing misuse of funds, and strengthening ethical values ​​of service. Independent audits and the formation of a financial team with integrity are crucial factors in realizing accountable fund management. In addition, transparency is not only an administrative obligation, but also a spiritual calling in maintaining the testimony of the church as the body of Christ. This study recommends the implementation of an open financial reporting system, strict internal supervision, and a culture of responsible service as real steps to encourage transparency in church governance.